Investigation on biomass steam gasification in a dual fluidized bed reactor with the granular kinetic theory. (December 2018) - Yan, Linbo; Cao, Yang; Zhou, Hongzhiyuan; He, Boshu
Highlights: A CFD model for the DFB reactor is built with the granular kinetic theory. The model is fully validated against a series of experimental data. The biomass steam gasification in the DFB reactor is comprehensively investigated. The optimal cold gas efficiency of the DFB reactor is 82.9%. The DFB cold gas efficiency is the most sensitive to biomass feeding rate. Abstract: The dual fluidized bed (DFB) reactor is promising to convert biomass into high-quality syngas efficiently. In this work, a three-dimensional model is built based on the granular kinetic theory to predict the biomass steam gasification in dual fluidized bed reactors. The model is firstly validated against a series of experimental results. Then, the effects of some essential operation parameters including the biomass flow rate ( F b ), the steam to fuel ratio ( R sf ) and the gasification temperature ( T g ) on the biomass steam gasification properties in a DFB reactor are comprehensively analyzed with the orthogonal method. In the concerned ranges of the operation parameters, the cold gas efficiency is found to be the most sensitive to F b and least sensitive to T g . The optimal cold gas efficiency of the DFB gasifier is 82.9% when F b, R sf and T g are 15 kg/h, 1.5 and 900 °C, respectively, and the H2 mole fraction is 46.62%.